Development of Portfolio Assessment Prototypes for Learning French Writing Class X High School Students - Sri Harini Ekowati; Yunilis Andika (Fakultas Bahasa dan Seni UNP, 2023)
Learning French writing is often considered a difficult lesson. Not only at the college level but also at the high school level. The difficulties experienced by students are usually related to grammar, orthography, vocabulary, and in finding ideas. One of the ways to overcome this difficulty is by practicing writing in French a lot. A significant way to practice is to use a portfolio assessment. This study aims to develop a portfolio assessment of French writing skills for class X SMA students. This portfolio assessment was developed based on Sugiyono's R&D model, while the method follows Kaur and Samad (2013). To find out whether the portfolio assessment is appropriate and appropriate for high school students to use, a survey was conducted by 5 French teachers in DKI Jakarta and its surroundings. This study concludes that the developed portfolio assessment changes are suitable for use in class.